Dissimilar Fitness Associated with Resistance to Fluoroquinolones Influences Clonal Dynamics of Various Multiresistant Bacteria - Fuzi, Miklos (Frontiers in Microbiology, 2016)
Fitness cost associated with resistance to fluoroquinolones was recently shown to vary across clones of methicillin-resistant Staphylococcus aureus and extended-spectrum β-lactamase-producing Klebsiella pneumoniae. The resulting dissimilar fitness should have influenced the clonal dynamics and thereby the rates of resistance for these pathogens. Moreover, a similar mechanism was recently proposed for the emergence of the H30 and H30R lineages of ESBL-producing E. coli and the major international clone (ribotype 027) of Clostridium difficile. Furthermore, several additional international clones of various multiresistant bacteria are suspect to have been selected by an analogous process. An ability to develop favorable mutations in the gyrase and topoisomerase IV genes seems to be a prerequisite for pathogens to retain fitness while showing high-level resistance to fluoroquinolones. Since, the consumption of other “non-fluoroquinolone” groups of antibiotics have also contributed to the rise in resistance rates a more judicious use of antibiotics in general and of fluoroquinolones in particular could ameliorate the international resistance situation.